Morphological Variation of Strychnos spinosa Lam. Morphotypes: A Case Study at Bonamanzi Game Reserve, KwaZulu-Natal, South Africa - Zoliswa Mbhele; Godfrey E. Zharare; Clemence Zimudzi; Nontuthuko R. Ntuli (Diversity, 2022)
Strychnos spinosa Lam. of the Loganiaceae family is associated with versatility, poverty eradication, and rural economic development. However, the morphological diversity of S. spinosa is not well documented. This limits efforts toward its improvement and commercial exploitation. This study aimed to characterize the variability, vegetative and reproductive traits, and heritability of S. spinosa morphotypes at Bonamanzi Game Reserve. The majority of the morphotypes had green, rough, round immature fruits with dark green, elongated, open fully developed leaves. Fruits varied between roundish and pyriform shape as well as green and purple colour. Positive correlation was mainly seen between fruit and seed traits. Principal component analysis indicated fruit and seed traits as major discriminating factors for morphotypes, followed by leaf size and seed thickness. A dendrogram primarily grouped morphotypes according to fruit texture. Genotypic variance and genotypic coefficient of variation were higher than environmental variance and environmental coefficient variation in reproductive traits of S. spinosa. A rough pericarp texture and purple tinge on the immature leaves of some morphotypes was recorded for the first time. Differences in morphological features across S. spinosa morphotypes indicate a high level of diversity that could be utilized by breeders to generate new cultivars. This first report on variability and heritability among S. spinosa morphotypes forms the basis of available germplasm essential for future breeding programs.